Eksistensi Masjid Pesisir Di Tengah Badai Covid-19 : (Studi Kasus: Masjid Pasa, Kota Pariaman) - Akdila Bulanov (Jurnal Masyarakat Maritim, 2021)
Masjid Pasa is located in the Preparatory Pariaman City. Masjid and strong traditional values ​​are able to compete in the midst of society that has experienced changes due to covid-19. Covid-19 does not rule out the possibility of eliminating the traditional values ​​of the Masjid. Existence can be maintained because of the ability of the Masjid to maintain the elements it has. This study uses a qualitative descriptive method. Data obtained from key informants and supporting informants. The results showed that, Masjid Pasa is still alive today, even though Masjid Pasa is in the midst of a society that has experienced changes and developments due to covid-19. The ability of the Masjid to keep its elements in balance with one another in the midst of modernization is the key to the sustainability of the Masjid.